Contrastive Analysis Study of Nominalization in 2024 Indonesian Presidential Candidates' Speeches - Yulianti, Deni Friska; Oktoviandry, Rifki (Universitas Negeri Padang, 2024)
This study aims to find the types and differences in nominalizations used in the speeches of the 2024 Indonesian presidential candidates: Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. Using data from a YouTube video hosted by CSIS Indonesia titled